Acute care nurses' perceptions of electronic health record use: A mixed method study. Issue 4 (7th May 2018) - Strudwick, Gillian; McGillis Hall, Linda; Nagle, Lynn; Trbovich, Patricia
Abstract: Aim: The overall aim of this study is to examine nurses' perceptions of electronic health record use in an acute care hospital setting. Design: This study uses a sequential mixed methods design in two phases. Methods: Phase one consists of a survey of Registered Nurses to understand nurses' perceptions of electronic health record use. Phase two is comprised of focus groups of a subsample from phase one. Data collection occurred from November 2015 ‐ August 2016 and was done in Toronto, Canada. Results: In phase one, navigation was found to be a predictor of nurses' perceptions of electronic health record use. In phase two, participants discussed the following five topics: (1) navigation; (2) functionality; (3) organizational standards; (4) documentation workload and (5) issues of system performance and response time. This study has implications for organizations implementing electronic health records, nursing leaders and electronic health record vendors.